Guidance on a Digital Factory Twin: Proposal for a Reference Architecture - Lick, Jonas; Kattenstroth, Fiona; Trienens, Malte; Disselkamp, Jan-Philipp; Kühn, Arno; Dumitrescu, Roman (2024 IEEE International Conference on Technology Management, Operations and Decisions (ICTMOD))

Franke-Reddig, Julia, „Bernard Bolzano im Kontext der Logikgeschichtsschreibung von Heinrich Scholz“, SieB. Siegener Beiträge zur Geschichte und Philosophie der Mathematik 18 (2024), 155–175 - Peckhaus, Volker (zbMATH Open, Zbl. 08058231)

Gaia-X in industriellen Wertschöpfungsnetzwerken – Erkenntnisse aus der Förderlinie InGAIA-X - Dumitrescu, Roman; Riedel, Oliver; Henke, Michael; Metternich, Joachim; Ihlenfeldt, Steffen; Koldewey, Christian (Gaia-X in industriellen Wertschöpfungsnetzwerken – Erkenntnisse aus der Förderlinie InGAIA-X)

Mit digitalen Hebeln zur Kreislaufwirtschaft - Rasor, Anja; Koldewey, Christian; Dumitrescu, Roman (Nachhaltige Industrie)

Vorausschau und Technologieplanung - 19. Symposium für Vorausschau und Technologieplanung

VCSELs: Influence of Design on Performance and Data Transmission over Multi-Mode and Single-Mode Fibers - Ledentsov, Nikolay N.; Ledentsov, Nikolay; Shchukin, Vitaly A.; Ledentsov, Alexander N.; Makarov, Oleg Yu.; Titkov, Ilya E.; Lindemann, Markus; de Adelsburg Ettmayer, Thomas; Gerhardt, Nils Christopher; Hofmann, Martin R.; Chen, Xin; Hurley, Jason E.; et al. (Photonics)
Substantial improvements in the performance of optical interconnects based on multi-mode fibers are required to support emerging single-channel data transmission rates of 200 Gb/s and 400 Gb/s. Future optical components must combine very high modulation bandwidths—supporting signaling at 100 Gbaud and 200 Gbaud—with reduced spectral width to mitigate chromatic-dispersion-induced pulse broadening and increased brightness to further restrict flux-confining area in multi-mode fibers and thereby increase the effective modal bandwidth (EMB). A particularly promising route to improved performance within standard oxide-confined VCSEL technology is the introduction of multiple isolated or optically coupled oxide-confined apertures, which we refer to collectively as multi-aperture (MA) VCSEL arrays. We show that properly designed MA VCSELs exhibit narrow emission spectra, narrow far-field profiles and extended intrinsic modulation bandwidths, enabling longer-reach data transmission over both multi-mode (MMF) and single-mode fibers (SMF). One approach uses optically isolated apertures with lateral dimensions of approximately 2–3 µm arranged with a pitch of 10–12 µm or less. Such devices demonstrate relaxation oscillation frequencies of around 30 GHz in continuous-wave operation and intrinsic modulation bandwidths approaching 50 GHz. Compared with a conventional single-aperture VCSELs of equivalent oxide-confined area, MA designs can reduce the spectral width (root mean square values < 0.15 nm), lower series resistance (≈50 Ω) and limit junction overheating through more efficient multi-spot heat dissipation at the same total current. As each aperture lases in a single transverse mode, these devices exhibit narrow far-field patterns. In combination with well-defined spacing between emitting spots, they permit tailored restricted launch conditions in MMFs, enhancing effective modal bandwidth. In another MA approach, the apertures are optically coupled such that self-injection locking (SIL) leads to lasing in a single supermode. One may regard one of the supermodes as acting as a master mode controlling the other one. Streak-camera studies reveal post-pulse oscillations in the SIL regime at frequencies up to 100 GHz. MA VCSELs enable a favorable combination of wavelength chirp and chromatic dispersion, extending transmission distances over MMFs beyond those expected for zero-chirp sources and supporting transfer bandwidths up to 60 GHz over kilometer-length SMF links.

Multimode vertical-cavity surface-emitting lasers under spin injection - Diiankova, Uliana; Drong, Mariusz; Pusch, Tobias; Michalzik, Rainer; Lindemann, Markus; Gerhardt, Nils Christopher; Hofmann, Martin R. (APL Photonics)
Recent research revealed that single-mode vertical-cavity surface-emitting lasers under spin injection (spin-VCSELs) have the potential to revolutionize laser technology for short-haul optical communications. While previous studies have focused solely on single-mode operation, this study introduces multimode spin-VCSELs. We experimentally demonstrate the existence of multi-resonant polarization dynamics when spin is injected, a phenomenon previously unobserved. The development opens the door to significantly faster and more efficient optical communication systems by harnessing the collective behavior of multiple laser modes. Furthermore, we lay the groundwork for understanding multimode operation through the extension of the single-mode spin–flip model, which forms the basis for present and future analyses of multimode spin-laser operation. This work is an important step toward realizing the full potential of spin-VCSELs and, thus, enables significantly improved performance of spin-VCSEL-based optical networks in the future.

Multiresolution analysis on spectra of hermitian matrices - Langen, Lukas; Rösler, Margit (Indagationes Mathematicae)
We establish a multiresolution analysis on the space $\text{Herm}(n)$ of $n× n$ complex Hermitian matrices which is adapted to invariance under conjugation by the unitary group $U(n).$ The orbits under this action are parametrized by the possible ordered spectra of Hermitian matrices, which constitute a closed Weyl chamber of type $A_{n-1}$ in $\mathbb R^n.$ The space $L^2(\text{Herm}(n))^{U(n)}$ of radial, i.e. $U(n)$-invariant $L^2$-functions on $\text{Herm}(n)$ is naturally identified with a certain weighted $L^2$-space on this chamber. The scale spaces of our multiresolution analysis are obtained by usual dyadic dilations as well as generalized translations of a scaling function, where the generalized translation is a hypergroup translation which respects the radial geometry. We provide a concise criterion to characterize orthonormal wavelet bases and show that such bases always exist. They provide natural orthonormal bases of the space $L^2(\text{Herm}(n))^{U(n)}.$ Furthermore, we show how to obtain radial scaling functions from classical scaling functions on $\mathbb R^{n}$. Finally, generalizations related to the Cartan decompositions for general compact Lie groups are indicated.

On norms on Harish-Chandra modules - Bernstein, Joseph; Ganguly, Pritam; Krötz, Bernhard; Kuit, Job; Sayag, Eitan
The Casselman-Wallach theorem is a foundational result in the theory of representations of real reductive groups connecting algebraic representations to topological representations. We provide a quantitative version of this theorem. For that we introduce the notion of {\it Sobolev gap} for a Harish-Chandra module. This is a new invariant whose finiteness is highly non-trivial. We determine the Sobolev gap for representations in the unitary dual of the group $\SL(2,\R)$ and establish uniform finiteness results in general for representations of the discrete series and the minimal principal series. We use these notions to reformulate and extend classical results of Bernstein and Reznikov concerning automorphic functionals with respect to cocompact lattices. In particular, we prove an abstract convexity bound which applies to automorphic functionals with respect to general lattices in $\SL(2,\R)$ and is independent of the type of unitarizable irreducible Harish-Chandra module. Finally, we offer an extensive list of open problems.

Generalized Positive Energy Representations of the Group of Compactly Supported Diffeomorphisms - Janssens, Bas; Niestijl, Milan (Communications in Mathematical Physics)
Abstract Motivated by asymptotic symmetry groups in general relativity, we consider projective unitary representations $$\overline{ρ }$$ ρ ¯ of the Lie group $${{\,Diff\,}}_c(M)$$ Diff c ( M ) of compactly supported diffeomorphisms of a smooth manifold M that satisfy a so-called generalized positive energy condition. In particular, this captures representations that are in a suitable sense compatible with a KMS state on the von Neumann algebra generated by $$\overline{ρ }$$ ρ ¯ . We show that if M is connected and $$\dim (M) > 1$$ dim ( M ) > 1 , then any such representation is necessarily trivial on the identity component $${{\,Diff\,}}_c(M)_0$$ Diff c ( M ) 0 . As an intermediate step towards this result, we determine the continuous second Lie algebra cohomology $$H^2_ct(\mathcal {X}_c(M), \mathbb {R})$$ H ct 2 ( X c ( M ) , R ) of the Lie algebra of compactly supported vector fields. This is subtly different from Gelfand–Fuks cohomology in view of the compact support condition.

Dung’s Argumentation Framework: Unveiling the Expressive Power with Inconsistent Databases - Mahmood, Yasir; Hecher, Markus; Ngonga Ngomo, Axel-Cyrille (Proceedings of the AAAI Conference on Artificial Intelligence)
The connection between inconsistent databases and Dung’s abstract argumentation framework has recently drawn growing interest. Specifically, an inconsistent database, involving certain types of integrity constraints such as functional and inclusion dependencies, can be viewed as an argumentation framework in Dung’s setting. Nevertheless, no prior work has explored the exact expressive power of Dung’s theory of argumentation when compared to inconsistent databases and integrity constraints. In this paper, we close this gap by arguing that an argumentation framework can also be viewed as an inconsistent database. We first establish a connection between subset-repairs for databases and extensions for AFs considering conflict-free, naive, admissible, and preferred semantics. Further, we define a new family of attribute-based repairs based on the principle of maximal content preservation. The effectiveness of these repairs is then highlighted by connecting them to stable, semi-stable, and stage semantics. Our main contributions include translating an argumentation framework into a database together with integrity constraints. Moreover, this translation can be achieved in polynomial time, which is essential in transferring complexity results between the two formalisms.

Analyzing the role of family socio-economic status, education and work characteristics in times of generative artificial intelligence and digital divide - Neufeld, Katharina; Ohly, Sandra; Sedefoglu-Ulucak, Didem; Steinhardt, Isabel; Mauermeister, Sylvi (Career Development International)
Purpose This study aims to explore the current state of generative artificial intelligence (genAI) in the workplace and discuss a potential digital divide in relation to genAI. Design/methodology/approach Using a quantitative approach, we study career-relevant predictors – family socio-economic status, education and work characteristics – and their relationship with different indicators of digital divide – access, genAI use, attitude toward AI and perceived AI literacy. To test our hypothesis, we used logistic and linear regression analyses. Additionally, latent profile analysis was conducted to identify patterns regarding work characteristics within the sample. Findings Among the 1,341 participants, 326 individuals were genAI users. Our results show that higher family socio-economic status, education and enriched and demanding work can be linked to a more positive attitude toward AI and higher perceived AI literacy. In the case of access and frequency of use, the results were mixed. Originality/value Our findings offer a novel contribution by examining a potentially upcoming digital divide in the case of genAI. We focus on how the career adaptation of the workforce might develop in the age of genAI. Importantly, we highlight that not all individuals may have an equal opportunity to adapt to genAI, which could hinder their future career development and reinforce patterns of inequality. Future research should address how to promote inclusivity and consider individual differences in adapting to genAI.

Laterally coupled vertical-cavity surface-emitting lasers with tunable resonance width and frequency - Lindemann, M.; D’Alessandro, M.; Ledentsov, N.; Makarov, O. Y.; Ledentsov, N. N.; Tibaldi, A.; Gerhardt, Nils Christopher; Hofmann, M. R. (Journal of Applied Physics)
Laterally coupled vertical-cavity surface-emitting lasers (VCSELs) can exhibit additional resonances at high modulation frequencies that can substantially increase the laser’s modulation bandwidth. State-of-the-art laterally coupled devices require non-standard manufacturing technology and precise tuning of the currents supplied to each cavity separately to form optical supermodes suitable for such resonances. Here, we report on a novel switching phenomenon in laterally coupled VCSEL structures having only a single common electric contact and manufactured in a standard oxide-confined VCSEL geometry. At lower currents, they can be operated in a weakly coupled (WCR) regime and, at higher currents, in an injection-locked (IL) regime, enabling fundamentally different spectral and dynamic features. In the WCR, both optical supermodes lase and a narrow tunable plasma-assisted peak at their beating frequency is observed for each of the apertures, with a current-dependent frequency tuning and anti-phase intensity oscillations in each of the cavities. In contrast, in the IL regimes, only one (anti-symmetric) supermode lases. This adds a broader resonance to the modulation response while the intensity oscillations in both cavities are in-phase. Only the IL regime can result in increased modulation bandwidth of the system. Measurements of the pulse responses and continuous modulation up to 70 GHz for both operational regimes are presented and compared with simulations of our distributed rate equation model whose parameters are extracted from full-wave electromagnetic simulations of the device, including the temperature distribution in the device. Excellent agreement is found and enables comprehensive understanding of the dynamics of supermodes in oxide-confined coupled cavity VCSELs.

Correlation between interlaminar shear strength of CFRP and joint strength of aluminium-CFRP hybrid joints - Wu, Shuang; Delp, Alexander; Freund, Jonathan; Walther, Frank; Haubrich, Jan; Löbbecke, Miriam; Tröster, Thomas (The Journal of Adhesion)
Fibre-reinforced polymers are increasingly used due to their high specific strength, making them suitable for local sheet metal reinforcement. This allows improved overall mechanical properties with reduced wall thickness of the sheet metal part and, thus, lower weight of the components. One of the main focuses of research into such hybrid structures is on the adhesive properties and the respective failure behaviour of the interfaces. Generally, the failure behaviour under the influence of mechanical loads can be divided into adhesive, cohesive and mixed-mode failure. The correlation between observed failure behaviour and adhesion properties of the hybrid composite materials is analysed in detail in this work. The hybrid composite consists of an aluminium sheet of the alloy EN AW‑6082 T6 and thermoset carbon fibre-reinforced plastic (CFRP) prepreg. The aluminium sheet was laser pretreated before hybrid production to improve the adhesion properties. The specimens studied were produced by the prepreg pressing process, in which the components are cured and joined simultaneously. The influences of the thickness of the CFRP part, the layup, the fibre orientation at the boundary layer, and the laser pretreatment parameters on the properties of the hybrid joints were investigated.
Keywords: Prepreg pressing process; hybrid joints; laser surface pretreatment; intrinsic manufacturing; CFRP; aluminium; materials engineering

A maturity based data management integration in engineering research projects - Wawer, Max Leo; Müller, Laura; Khaled, Jaouhar Ben; Stauß, Timo; Wurst, Johanna; Mozgova, Iryna; Lachmayer, Roland (Proceedings of the Design Society)
With the increasing amount of data in collaborative engineering research, the need for effective and efficient data management is growing. This paper uses a maturity-based process model to examine the implementation of research data management (RDM) in engineering projects. A process model visualizes a research-supported implementation of RDM and helps researchers evaluate their data management strategies through maturity level assessment. For this approach, activities are assigned to different maturity levels based on a maturity level characteristic providing a differentiated view of the implementation of RDM. An example from an ongoing project shows the application and support of the developed maturity-based process model. The work emphasizes the importance of standardized and quality-assured data management for the success of research projects and their contribution to the scientific community

Getting Things Done: How to Make Simulation Data FAIR and Ready to Reuse - Müller, Laura; Hinterthaner, Marc; Ortlieb, Eduard; Mohnfeld, Norman; Schultz, Andreas Maximilian; Uhe, Johanna; Koepler, Oliver; Mozgova, Iryna (IFIP Advances in Information and Communication Technology)

Strukturierte FDM-Plattformen: Aktuelle Lösungen und Herausforderungen in Informationsinfrastrukturprojekten - Schultz, Andreas Maximilian; Mozgova, Iryna; Altun, Osman; Karras, Oliver; Koepler, Oliver; Müller, Laura; Nuenberger, Florian; Röwenstrunk, Daniel; Wawer, Max Leo

Quantitative research on SDGs and HRM - Yang, Philip (The Elgar Companion to Human Resource Management Beyond the Sustainable Development Goals)

Wie Performance Management das Engagement steigern kann - Ehmann, Stefanie; Kampkötter, Patrick; Maier, Patrick; Yang, Philip (Controlling & Management Review)

Data Literacy im Wissenschaftsjournalismus – Facetten journalistischer Datenkompetenz und Fortbildungsbausteine zu deren Schulung - Binder, Karin; Vogel, Markus